Intruksi Presiden Sebagai Hasil dari Upaya Mediasi Konflik di Konflik Poso - Hanifah, Ida (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2022)
The purpose of this writing is to find out and analyze how the President's Instructions are an effort to mediate conflict in the Poso conflict. The research method in this paper uses the method of library research (library research) obtained from various sources of literature (books, literature, articles, magazines, websites, journals, research results and so on) with qualitative data analysis. The results of this study concluded that there were two main factors that became the basis for the conflict in Poso, namely the dominance of religion and the transfer of power both economically, socially and politically. By making efforts to resolve the representation between the two parties in order to find peace, then the Presidential Instruction No. policy was issued. 14 of 2005 which consists of: 1) In carrying out handling of Poso must be coordinated in an integrated and comprehensive manner. 2) Every case of crime and terror must be handle firmly. 3) In carrying out the handling efforts, he still pays attention to the Malino Declaration on December 20, 2001.